2021
DOI: 10.7759/cureus.14942
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Ophthalmological Findings in Hospitalized COVID-19 Patients

Abstract: Introduction: The symptoms of coronavirus disease-19 (COVID-19) may range from mild to severe. Patients usually present with fever, cough, and other respiratory tract symptoms, but may also be asymptomatic. Some studies have also indicated the ocular involvement by the virus. This study aims to look deeply into all ophthalmic findings seen in COVID-19 patients and their clinical characteristics.Methods: This longitudinal study was conducted in the COVID-19 unit of a tertiary care hospital, Pakistan. Data of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(26 reference statements)
0
5
0
Order By: Relevance
“… 13 Conjunctival irritation was the most prevalent ophthalmological finding (50.8%), followed by diplopia (27.8%) and cotton wool patches (27.8%). 14 Males have been diagnosed with viral conjunctivitis at a higher rate than females. 15 The majority of the cases were acute COVID-19 cases, with some chronic COVID-19 cases observed in each case.…”
mentioning
confidence: 99%
“… 13 Conjunctival irritation was the most prevalent ophthalmological finding (50.8%), followed by diplopia (27.8%) and cotton wool patches (27.8%). 14 Males have been diagnosed with viral conjunctivitis at a higher rate than females. 15 The majority of the cases were acute COVID-19 cases, with some chronic COVID-19 cases observed in each case.…”
mentioning
confidence: 99%
“… 3 , 4 , 5 Among the variety of ophthalmic manifestations described, manifestations similar to those reported in population-based studies were found, as well as in case reports. 4 , 5 , 6 , 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…Most studies have emphasized respiratory symptoms, yet there is evidence pointing to potential eye complications ( Seah and Agrawal, 2020 ). Research indicates that keratoconjunctivitis ( Hutama et al, 2022 ), conjunctivitis ( Chen et al, 2020 , Maychuk et al, 2020 , Wu et al, 2020 ), conjunctival irritation, diplopia and cotton wool patches are among the most prevalent ophthalmic symptoms in COVID-19 patients ( Khan et al, 2021 ). Notably, viral conjunctivitis has been observed to affect men more frequently than women ( Al-Namaeh, 2021 ).…”
Section: Introductionmentioning
confidence: 99%